Рiroctone olamine determination in bulk by UV spectrophotometric method - Antypenko, L. M.; Solodovnyk, V. A.; Антипенко, Людмила Миколаївна; Солодовник, Віталій Андрійович (Х. : НФаУ, 2017)
Introduction: The piroctone olamine is 1-hydroxy-4-methyl-6-(2,4,4-trimethyl)-pentyl-2(1H)-pyridone 2-aminoethanol salt. Under the brand name Octopirox, it was used for the first time in the Seborin produced by Schwarz-kopf & Henkel Düsseldorf (subsidiary of Hoechst). Nowadays, the compound is contained in many cosmetic products for the treatment of dandruff (Pityriasis simplex capillitii).
Keywords: тези